Carbon Monoxide as a Toxic Agent in Charcoal Briquette-Related Deaths: A Systematic Literature Review - Aliifah, Khansa; Marisa, Hilma; Lestari, Indah; Septiani, Jelita; Putri Kusumawardhani, Khalyssa; Larasati Setyaningrum, Dwi (Jurusan Farmasi Universitas Negeri Gorontalo, 2025)
Carbon monoxide (CO) is a colorless, odorless, and tasteless toxic gas that poses a substantial health hazard, particularly in enclosed environments. Combustion of charcoal briquettes is a frequently overlooked source of CO exposure, linked to both accidental and intentional fatalities. This review synthesizes current evidence on the toxicological role of CO in charcoal briquette-related deaths and identifies preventive strategies. A systematic literature review was conducted using PubMed, ScienceDirect, and Google Scholar to identify peer-reviewed articles published between January 2020 and April 2025. Studies in English or Indonesian reporting fatal CO poisoning cases associated with charcoal briquette combustion were included, provided they contained data on carboxyhemoglobin (COHb) levels, clinical presentation, and environmental risk factors. Ten studies met the inclusion criteria. Most fatal cases occurred in enclosed or poorly ventilated spaces, with COHb levels exceeding 30%, a threshold strongly associated with mortality. Common clinical manifestations included headache, confusion, loss of consciousness, seizures, and respiratory distress. Autopsy findings frequently revealed cherry-red discoloration of the skin and mucous membranes. Both accidental and intentional exposures were reported, with men disproportionately affected. Charcoal briquette combustion in confined environments remains a significant and preventable cause of CO-related mortality. Public awareness campaigns, mandatory installation of CO detectors, and ventilation standards are critical to reducing the incidence of such deaths.